Lithium cobalt oxide positive electrode material and preparation method and application thereof
By adjusting the grade mixing process of lithium cobaltate positive materials, first mix large and small particles with the covering agent, and then mix and sintering, solve the problem of unstable circulation performance of the material under high voltage, and realize the coverage of covering. Increased controllability of doses and improvement of material performance.
Patent Information
- Application Number
- CN202310888501.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
AI Technical Summary
The existing lithium cobalt oxide positive electrode materials have unstable cycling performance at high voltages, and the surface coatings of large and small particles are uncontrollable, affecting the capacity and cycling performance of the material.
By adjusting the large and small particle gradation mixing process, first mix the first lithium cobalt oxide fired product and the second lithium cobalt oxide fired product respectively with the coating agent, and then perform blending and sintering to ensure uniform distribution of the coating agent.
It achieves controllability of the distribution of coating agents on the surface of large and small particles, improves the capacity and cycle performance of the material, and ensures stable electrochemical performance under high voltage.
Smart Images

Figure CN119340350A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a lithium cobalt oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous development of electric vehicles and consumer electronics, people have higher and higher requirements for the energy density of lithium-ion batteries. By increasing the charging voltage, the released capacity density and energy density can be effectively improved. However, there are many problems with the cycle performance of materials under high voltage, such as unstable material structure, dissolution of active substances, and accumulation of inert substances on the surface of materials, which make it difficult for lithium cobalt oxide batteries to show ideal performance under high voltage. Therefore, in order to enable lithium cobalt oxide batteries to circulate stably under high voltage, doping and coating methods are generally used to modify the positive electrode material. The coating can effectively improve the cycle stability of lithium cobalt oxide materials, reduce side reactions with the electrolyte, and increase the service life of the material.
[0003] However, as the charge cut-off voltage increases, the occurrence of side reactions on the electrode surface and the decay of the lithium cobalt oxide structure will be aggravated, thereby reducing its electrochemical performance. Surface coating is an effective way to improve the above problems, but too thick or too thin a coating layer will affect the material performance. If the coating layer is too thick, the capacity of the material will be low, and if the coating layer is too thin, the cycle performance of the material will decrease. The prior art uses a large and small particle grading process to increase the compaction density of the material, which can make the material have a higher energy density. Conventional lithium cobalt oxide preparation methods generally use multi-stage sintering, and the grading of large and small particles and the mixing of additives are carried out during the second sintering process.
[0004] However, due to the large difference in specific surface area between large particles and small particles, when large particles, small particles and coating additives are mixed together, the amount of coating on the surface of large and small particles will be different, and there will be
[0005] Small particles rub off the additives on the surface of large particles, resulting in a large difference in the coating layer on the surface of large and small particles and a decrease in material performance.
[0006] Based on the above research, it is necessary to provide a method for preparing a lithium cobalt oxide positive electrode material, wherein the preparation method makes the coating layer of particles of different sizes controllable, thereby ensuring the capacity of the material while improving the cycle performance of the material. Summary of the invention
[0007] The object of the present invention is to provide a lithium cobalt oxide positive electrode material and a preparation method and application thereof. The preparation method balances the distribution of coating substances in the lithium cobalt oxide material by adjusting the mixing process of large and small particle grading, so that the content of coating agents on the surfaces of different particles can be controlled, thereby solving the problems of poor material stability and uncontrollable surface coating layers of large and small particles during blending, and improving the capacity and cycle performance of the material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, a method for preparing a lithium cobalt oxide positive electrode material comprises the following steps:
[0010] (1) mixing a first lithium cobalt oxide sintered product with a coating agent to obtain a first mixture;
[0011] (2) mixing the second lithium cobalt oxide calcined product with a coating agent to obtain a second mixture;
[0012] The particle size D50 of the second lithium cobalt oxide sintered product is smaller than the particle size D50 of the first lithium cobalt oxide sintered product in step (1);
[0013] (3) mixing and sintering the first mixture of step (1) and the second mixture of step (2) to obtain the lithium cobalt oxide positive electrode material;
[0014] There is no particular order in which steps (1) and (2) are performed.
[0015] The first lithium cobalt oxide calcined product of the present invention is a large particle, and the second lithium cobalt oxide calcined product is a small particle. When the large and small particles are mixed and graded, the large and small particles are first mixed with the coating agent respectively, and the obtained mixture is then blended and sintered. Compared with mixing the large particles and the small particles with the coating agent together, the problem of uneven distribution of the coating agent on the particle surface due to the large difference in specific surface area between the large and small particles and the coating agent adsorbed on the particle surface falling off after blending is avoided, thereby improving the capacity and cycle performance of the positive electrode material.
[0016] Preferably, the mixing speed in step (1) and the mixing speed in step (2) are each independently greater than the mixing speed in step (3).
[0017] In the mixing process of the present invention, high-speed mixing is first performed separately and then low-speed blending is performed, which not only ensures the uniformity of the distribution of the coating agent on the particle surface, but also avoids the problem of rubbing off the coated coating agent during blending, further ensuring the mixed coating effect of the present invention.
[0018] Preferably, the mixing speed of step (1) and the mixing speed of step (2) are independently 3.25-8 times the mixing speed of step (3), for example, 3.25 times, 4 times, 5 times, 6 times, 7 times or 8 times, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, the mixing speed in step (1) is 1300-1600 rpm / min, for example, 1300 rpm / min, 1400 rpm / min, 1500 rpm / min or 1600 rpm / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the mixing time in step (1) is 10-30 min, for example, 10 min, 20 min or 30 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] Preferably, in step (1), the particle size D50 of the first lithium cobalt oxide sintered product is 16-19 μm, for example, 16 μm, 17 μm, 18 μm or 19 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] Preferably, based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total addition amount of the coating agent in step (1) and the coating agent in step (2) is 4-10wt%, for example, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the second lithium cobalt oxide sintered product in step (2).
[0024] On the basis of step-by-step mixing, the present invention also fully considers the problem that different particles have different particle sizes, resulting in different specific surface areas of the particles. Therefore, the present invention makes the amount of coating agent added correspond to the specific surface area, so that different particles are matched with different coating doses, thereby improving the uniformity of distribution of the coating agent on the surfaces of different particles and further improving the mixed coating effect.
[0025] Preferably, the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is 1:(2-6), for example, it can be 1:2, 1:3, 1:4, 1:5 or 1:6, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the coating agents in step (1) and step (2) respectively and independently include any one or a combination of at least two of a Li-containing compound, a Mg-containing compound, an Al-containing compound, a Zr-containing compound, a Ti-containing compound, a Co-containing compound, a F-containing compound, a Y-containing compound or a La-containing compound.
[0027] Preferably, in step (1), the first lithium cobalt oxide sintered product is prepared by the following method:
[0028] The lithium source, the first cobalt source and the dopant are mixed and calcined once to obtain the first lithium cobaltate calcined product.
[0029] Preferably, the primary calcination temperature is 1000-1200°C, such as 1000°C, 1100°C or 1200°C, the time is 6-12h, such as 6h, 8h, 10h or 12h, and the atmosphere is air atmosphere or oxygen atmosphere.
[0030] Preferably, the mixing speed in step (2) is 1300-1600 rpm / min, for example, 1300 rpm / min, 1400 rpm / min, 1500 rpm / min or 1600 rpm / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the mixing time in step (2) is 10-30 min, for example, 10 min, 20 min or 30 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Preferably, in step (2), the particle size D50 of the second lithium cobalt oxide sintered product is 4-8 μm, for example, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0033] Preferably, in step (2), the second lithium cobalt oxide sintered product is prepared by the following method:
[0034] Mixing a lithium source, a second cobalt source and a dopant and performing secondary calcination to obtain the second lithium cobaltate calcined product;
[0035] Preferably, the secondary calcination temperature is 900-1100°C, such as 900°C, 1000°C or 1100°C, the time is 6-12h, such as 6h, 8h, 10h or 12h, and the atmosphere is air atmosphere or oxygen atmosphere.
[0036] The first cobalt source and the second cobalt source of the present invention are respectively a large-particle cobalt source and a small-particle cobalt source. The present invention does not specifically limit the large-particle cobalt source and the small-particle cobalt source. Those skilled in the art can reasonably select them according to the particle size D50 of the first lithium cobaltate sintered product and the second lithium cobaltate sintered product.
[0037] Based on the mass of the sintered product, the doping amount of the dopant of the present invention is 1-3wt%, and the dopant includes any one of a Li-containing compound, a Mg-containing compound, an Al-containing compound, a Zr-containing compound, a Ti-containing compound, a Co-containing compound, a F-containing compound, a Y-containing compound or a La-containing compound, or a combination of at least two thereof.
[0038] Preferably, the mixing speed in step (3) is 200-400 rpm / min, for example, 200 rpm / min, 250 rpm / min, 300 rpm / min, 350 rpm / min or 400 rpm / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] The first mixture and the second mixture of the present invention need to be mixed at a low speed. If the mixing speed is too high, the coating agent on the surface of the first mixture and the second mixture will fall off, reducing the coating effect. If the mixing speed is too low, the grading effect will be affected. Therefore, the present invention adopts a specific mixing speed to ensure both the grading effect and the coating effect.
[0040] Preferably, the mixing time in step (3) is 10-20 min, for example, 10 min, 15 min or 20 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, in step (3), the mass ratio of the first mixture to the second mixture is (5-9):(1-5), for example, it can be 5:5, 7:9 or 9:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the sintering temperature in step (3) is 800-1000°C, for example, 800°C, 900°C or 1000°C, the sintering time is 5-16h, for example, 5h, 10h, 15h or 16h, and the atmosphere is air atmosphere or oxygen atmosphere.
[0043] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:
[0044] (1) mixing a coating agent and a first lithium cobalt oxide sintered product having a particle size D50 of 16-19 μm at a speed of 1300-1600 rpm / min for 10-30 min, wherein the mixing speed is 3.25-8 times the mixing speed in step (3), to obtain a first mixture;
[0045] The first lithium cobalt oxide sintered product is prepared by the following method: a lithium source, a first cobalt source and a dopant are mixed, and then calcined at a temperature of 1000-1200° C. for 6-12 hours in an air atmosphere or an oxygen atmosphere to obtain the first lithium cobalt oxide sintered product;
[0046] (2) mixing the coating agent and the second lithium cobalt oxide calcined product having a particle size D50 of 4-8 μm at a speed of 1300-1600 rpm / min for 10-30 min, wherein the mixing speed is 3.25-8 times the mixing speed of step (3), to obtain a second mixture;
[0047] The second lithium cobalt oxide sintered product is prepared by the following method: a lithium source, a second cobalt source and a dopant are mixed, and then secondary calcined at a temperature of 900-1100° C. for 6-12 hours in an air atmosphere or an oxygen atmosphere to obtain the second lithium cobalt oxide sintered product;
[0048] Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total amount of the coating agent in step (1) and the coating agent in step (2) is 4-10wt%; the ratio of the amount of the coating agent in step (1) to the amount of the coating agent in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the second lithium cobalt oxide sintered product in step (2);
[0049] (3) mixing the first mixture of step (1) and the second mixture of step (2) at a mass ratio of (5-9):(1-5) at a speed of 200-400 rpm / min for 10-20 min, and then sintering at a temperature of 800-1000° C. for 5-16 h in an air atmosphere or an oxygen atmosphere to obtain the lithium cobalt oxide positive electrode material;
[0050] There is no particular order in which steps (1) and (2) are performed.
[0051] In a second aspect, the present invention provides a lithium cobalt oxide positive electrode material, wherein the lithium cobalt oxide positive electrode material is prepared by the preparation method described in the first aspect.
[0052] In a third aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the lithium cobalt oxide positive electrode material as described in the second aspect.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The present invention adjusts the mixing process, firstly mixes the first lithium cobalt oxide calcined product and the second lithium cobalt oxide calcined product with the coating agent respectively, and then blends the obtained mixture. Compared with the process of simply mixing large and small particle semi-finished products with the coating agent, this separate mixing process can avoid the problem of different coating layer thickness caused by different amounts of coating agent on the particle surface due to the difference in particle specific area; and compared with the process of separate coating and separate sintering followed by grading, the process of separate coating and grading followed by sintering of the present invention can make the large and small particles have better adsorption during the sintering process, and can achieve the purpose of reducing the polarization of the lithium cobalt oxide positive electrode material and improving the cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a scanning electron microscope image of the lithium cobalt oxide positive electrode material described in Example 1 of the present invention;
[0056] Figure 2 This is a scanning electron microscope image of the mixture in step (3) of Example 1 of the present invention;
[0057] Figure 3 This is a scanning electron microscope image of the lithium cobalt oxide positive electrode material described in Comparative Example 1 of the present invention;
[0058] Figure 4 This is a scanning electron microscope image of the mixed material described in Comparative Example 1 of the present invention;
[0059] Figure 5 This is a scanning electron microscope image of the lithium cobalt oxide positive electrode material described in Comparative Example 2 of the present invention;
[0060] Figure 6 This is a capacity retention rate curve of the battery made of the lithium cobalt oxide positive electrode material described in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0064] (1) mixing a coating agent and a first lithium cobalt oxide sintered product having a particle size D50 of 18 μm at a speed of 1500 rpm / min for 20 min, wherein the mixing speed is 5 times the mixing speed in step (3), to obtain a first mixture, wherein the coating agent is titanium oxide;
[0065] The first lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, magnesium oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then calcined at a temperature of 1100° C. for 10 hours in an air atmosphere to obtain the first lithium cobalt oxide calcined product, wherein the doping amount of magnesium oxide in the first lithium cobalt oxide calcined product is 2wt%;
[0066] (2) mixing the coating agent with a second lithium cobalt oxide sintered product having a particle size D50 of 6 μm at a speed of 1500 rpm / min for 20 min, wherein the mixing speed is 5 times the mixing speed in step (3), to obtain a second mixture, wherein the coating agent is titanium oxide;
[0067] The second lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, magnesium oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then secondary calcined at a temperature of 1000° C. for 8 hours in an air atmosphere to obtain the second lithium cobalt oxide calcined product, wherein the doping amount of magnesium oxide in the second lithium cobalt oxide calcined product is 2wt%;
[0068] Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total amount of the coating agent in step (1) and the coating agent in step (2) is 6wt%; the ratio of the amount of the coating agent in step (1) to the amount of the coating agent in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), which is 1:4;
[0069] (3) mixing the first mixture of step (1) and the second mixture of step (2) at a mass ratio of 7:3 at a speed of 300 rpm / min for 15 minutes to obtain a mixture, and then sintering the mixture at a temperature of 900° C. for 10 hours in an oxygen atmosphere to obtain the lithium cobalt oxide positive electrode material;
[0070] Among them, step (1) and step (2) are in no particular order;
[0071] The scanning electron microscope image of the lithium cobalt oxide positive electrode material obtained in this example is as follows Figure 1 As shown, the scanning electron microscope image of the mixture in step (3) is as follows Figure 2 As shown, the capacity retention rate curve of the battery made of the lithium cobalt oxide positive electrode material is as follows Figure 6 shown.
[0072] Example 2
[0073] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0074] (1) mixing a coating agent and a first lithium cobalt oxide sintered product having a particle size D50 of 16 μm at a speed of 1300 rpm / min for 30 min, wherein the mixing speed is 6.5 times the mixing speed in step (3), to obtain a first mixture, wherein the coating agent is zirconium oxide;
[0075] The first lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, lanthanum oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then calcined at 1000° C. for 12 hours in an air atmosphere to obtain the first lithium cobalt oxide calcined product, wherein the doping amount of lanthanum oxide in the first lithium cobalt oxide calcined product is 1wt%;
[0076] (2) mixing the coating agent with a second lithium cobalt oxide sintered product having a particle size D50 of 8 μm at a speed of 1600 rpm / min for 10 min, wherein the mixing speed is 8 times the mixing speed in step (3), to obtain a second mixture, wherein the coating agent is zirconium oxide;
[0077] The second lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, lanthanum oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then secondary calcined at a temperature of 1100° C. for 6 hours in an air atmosphere to obtain the second lithium cobalt oxide calcined product, wherein the doping amount of lanthanum oxide in the second lithium cobalt oxide calcined product is 1wt%;
[0078] Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total amount of the coating agent in step (1) and the coating agent in step (2) is 10wt%; the ratio of the amount of the coating agent in step (1) to the amount of the coating agent in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), which is 1:2;
[0079] (3) mixing the first mixture of step (1) and the second mixture of step (2) at a mass ratio of 1:1 at a speed of 200 rpm / min for 20 minutes, and then sintering at a temperature of 1000° C. for 5 hours in an air atmosphere to obtain the lithium cobalt oxide positive electrode material;
[0080] There is no particular order in which steps (1) and (2) are performed.
[0081] Example 3
[0082] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0083] (1) mixing a coating agent and a first lithium cobalt oxide sintered product having a particle size D50 of 19 μm at a speed of 1600 rpm / min for 10 min, wherein the mixing speed is 4 times the mixing speed in step (3), to obtain a first mixture, wherein the coating agent is titanium oxide;
[0084] The first lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, magnesium oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then calcined at a temperature of 1200° C. for 6 hours in an air atmosphere to obtain the first lithium cobalt oxide calcined product, wherein the doping amount of magnesium oxide in the first lithium cobalt oxide calcined product is 3wt%;
[0085] (2) mixing the coating agent and the second lithium cobalt oxide sintered product having a particle size D50 of 4 μm at a speed of 1300 rpm / min for 30 min, wherein the mixing speed is 3.25 times the mixing speed in step (3), to obtain a second mixture, wherein the coating agent is titanium oxide;
[0086] The second lithium cobalt oxide calcined product is prepared by the following method: lithium hydroxide, magnesium oxide and cobalt oxide containing 0.08 mol% Al are mixed, and then secondary calcined at 900° C. for 12 hours in an oxygen atmosphere to obtain the second lithium cobalt oxide calcined product, wherein the doping amount of magnesium oxide in the second lithium cobalt oxide calcined product is 3wt%;
[0087] Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total amount of the coating agent in step (1) and the coating agent in step (2) is 4wt%; the ratio of the amount of the coating agent in step (1) to the amount of the coating agent in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), which is 1:6;
[0088] (3) mixing the first mixture of step (1) and the second mixture of step (2) at a mass ratio of 9:1 at a speed of 400 rpm / min for 10 minutes, and then sintering at a temperature of 800° C. for 16 hours in an oxygen atmosphere to obtain the lithium cobalt oxide positive electrode material;
[0089] There is no particular order in which steps (1) and (2) are performed.
[0090] Example 4
[0091] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1 except that the mixing speeds in step (1), (2) and (3) are the same, all of which are 1500 rpm / min.
[0092] Example 5
[0093] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1 except that the mixing speeds in step (1), (2) and (3) are the same, all of which are 300 rpm / min.
[0094] Example 6
[0095] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1, except that the mixing speeds in step (1) and step (2) are both 300 rpm / min, and the mixing speed in step (3) is 1500 rpm / min.
[0096] Example 7
[0097] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1 except that the mixing speed in step (3) is 100 rpm / min.
[0098] Example 8
[0099] This embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1 except that the mixing speed in step (3) is 500 rpm / min.
[0100] Example 9
[0101] The present embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1, except that the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is 1:5.5, and the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the specific surface area of the second lithium cobalt oxide sintered product in step (2) is different.
[0102] Example 10
[0103] The present embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1, except that the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is 1:1, and the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the second lithium cobalt oxide sintered product in step (2) is different.
[0104] Embodiment 11
[0105] The present embodiment provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as that of Embodiment 1, except that the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is 1:7, and the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the specific surface area of the second lithium cobalt oxide sintered product in step (2) is different.
[0106] Comparative Example 1
[0107] This comparative example provides a method for preparing a lithium cobalt oxide positive electrode material, the preparation method comprising the following steps:
[0108] A coating agent, a first lithium cobalt oxide sintered product with a particle size D50 of 18 μm, and a second lithium cobalt oxide sintered product with a particle size D50 of 6 μm are mixed at a speed of 1500 rpm / min for 20 minutes to obtain a mixture, and then the mixture is sintered at a temperature of 900° C. for 10 hours in an oxygen atmosphere to obtain the lithium cobalt oxide positive electrode material, wherein the mass ratio of the first lithium cobalt oxide sintered product to the second lithium cobalt oxide sintered product is 7:3, and the coating agent is titanium oxide;
[0109] Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total addition amount of the coating agent in step (1) and the coating agent in step (2) is 6wt%;
[0110] The preparation methods of the first lithium cobalt oxide sintered product and the second lithium cobalt oxide sintered product are the same as those in Example 1;
[0111] The scanning electron microscope image of the lithium cobalt oxide positive electrode material obtained in this comparative example is as follows Figure 3 As shown, the scanning electron microscope image of the mixture is as shown Figure 4 As shown, the capacity retention rate curve of the battery made of the lithium cobalt oxide positive electrode material is as follows Figure 6 shown.
[0112] Comparative Example 2
[0113] This comparative example provides a method for preparing a lithium cobalt oxide positive electrode material. The preparation method is the same as Example 1 except that step (3) is changed.
[0114] The step (3) of this comparative example is: sintering the first mixture of step (1) at 900° C. for 10 h in an oxygen atmosphere to obtain a first sintered material; sintering the second mixture of step (2) at 900° C. for 10 h in an oxygen atmosphere to obtain a second sintered material; mixing the first sintered material and the second sintered material at a mass ratio of 7:3 at a speed of 300 rpm / min for 15 min to obtain the lithium cobalt oxide positive electrode material;
[0115] The scanning electron microscope image of the lithium cobalt oxide positive electrode material obtained in this comparative example is as follows Figure 5 As shown, the capacity retention rate curve of the battery made of the lithium cobalt oxide positive electrode material is as follows Figure 6 shown.
[0116] The lithium cobalt oxide positive electrode material obtained in the above examples and comparative examples and the lithium sheet negative electrode, The separator and LiPF6 electrolyte were prepared into button cells, and the battery capacity was characterized at 25°C and 3.0-4.5V. The capacity retention rate after 50 cycles at 0.5C rate and 3.0-4.55V was tested at 45°C and 0.5C rate.
[0117] The test results are shown in Table 1:
[0118] Table 1
[0119]
[0120]
[0121] From Table 1 we can see that:
[0122] The lithium cobalt oxide positive electrode material obtained by the present invention has excellent electrochemical properties. After the battery is made, the 0.1C capacity is above 185.4 mAh / g, the 0.5C capacity is above 176.0 mAh / g, the 1C capacity is above 171.1 mAh / g, and the capacity retention rate of 50 cycles at 45°C is above 83%; it can be seen from Example 1 and Comparative Examples 1-2 that no matter whether it is a blending method or a method of separate mixing, separate sintering and then grading, the effect of separate mixing and sintering together of the present invention cannot be achieved; it can be seen from Example 1 and Examples 4-8 that the present invention preferably mixes at a high speed when separately mixing, and preferably mixes at a low speed when grading, and the speed of the low-speed mixing is within a specific range, which can further improve the performance of the battery; it can be seen from Examples 1 and Examples 9-11 that the amount of coating agent added in the present invention should match the specific surface area of the particles. Even if the total amount added is within a reasonable range and the addition ratio is within a reasonable range, but it does not match the specific surface area, the effect of separate mixing cannot be achieved.
[0123] At the same time, combined Figure 2 and Figure 4It can be seen that in the conventional method of mixing all the substrates together, the surface coating of the additives on the large particles is uneven, and the surface coating of the additives on the small particles is relatively more ( Figure 4 ),contrast Figure 2 It can be seen that after the large particles and small particles are mixed evenly with the additives, they are graded and mixed in a certain proportion. This mixing method can improve the uniformity of the additive coating on the surface of large and small particles; combined with Figure 3 It can be seen that the method of mixing large and small particle substrates and coating additives together has an uneven particle surface and an island phenomenon caused by uneven coating of additives; Figure 5 It can be seen that the large particles are first mixed with the additives and then sintered, and then the small particles are mixed with the additives and sintered, and finally the sintered products of the two are mixed in a certain proportion to obtain the lithium cobalt oxide positive electrode material. In this way, it will be found that the large and small particles are not evenly distributed, and the small particles are easily adsorbed on the surface of the large particles, which will affect the homogenization effect in the later battery preparation process; Figure 1 It can be seen that the large particles and additives are first mixed evenly but not sintered, and then the small particles are mixed evenly but not sintered. Finally, the mixed products of the two are graded and mixed at a low speed in a certain proportion, and then sintered to obtain the lithium cobalt oxide positive electrode material. It can be seen that the surfaces of both large and small particles are relatively smooth, and the uniform distribution between large and small particles can be guaranteed.
[0124] In summary, the present invention provides a lithium cobalt oxide positive electrode material and a preparation method and application thereof. The preparation method balances the distribution of coating substances in the lithium cobalt oxide material by adjusting the large and small particle grading mixing process, so that the content of coating agents on the surfaces of different particles can be controlled, thereby solving the problems of poor material stability and uncontrollable surface coating layers of large and small particles during blending, and improving the capacity and cycle performance of the material.
[0125] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium cobalt oxide positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing a first lithium cobalt oxide sintered product with a coating agent to obtain a first mixture; (2) mixing the second lithium cobalt oxide calcined product with a coating agent to obtain a second mixture; The particle size D50 of the second lithium cobalt oxide sintered product is smaller than the particle size D50 of the first lithium cobalt oxide sintered product in step (1); (3) mixing and sintering the first mixture of step (1) and the second mixture of step (2) to obtain the lithium cobalt oxide positive electrode material; There is no particular order in which steps (1) and (2) are performed.
2. The preparation method according to claim 1, characterized in that: The mixing speed of step (1) and the mixing speed of step (2) are each independently greater than the mixing speed of step (3); Preferably, the mixing speed in step (1) and the mixing speed in step (2) are independently 3.25-8 times the mixing speed in step (3); Preferably, the mixing speed in step (1) is 1300-1600 rpm / min; Preferably, the mixing time in step (1) is 10-30 min.
3. The preparation method according to claim 1 or 2, characterized in that: Step (1) the particle size D50 of the first lithium cobalt oxide sintered product is 16-19 μm; Preferably, based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total addition amount of the coating agent in step (1) and the coating agent in step (2) is 4-10wt%; Preferably, the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the second lithium cobalt oxide sintered product in step (2); Preferably, the ratio of the amount of the coating agent added in step (1) to the amount of the coating agent added in step (2) is 1:(2-6).
4. The preparation method according to any one of claims 1 to 3, characterized in that The coating agent in step (1) and the coating agent in step (2) respectively and independently include any one or a combination of at least two of a Li-containing compound, a Mg-containing compound, an Al-containing compound, a Zr-containing compound, a Ti-containing compound, a Co-containing compound, a F-containing compound, a Y-containing compound or a La-containing compound; Preferably, in step (1), the first lithium cobalt oxide sintered product is prepared by the following method: Mixing a lithium source, a first cobalt source and a dopant and calcining the mixture to obtain the first lithium cobaltate calcined product; Preferably, the primary calcination is carried out at a temperature of 1000-1200° C., for a time of 6-12 hours, in an atmosphere of air or oxygen.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The mixing speed in step (2) is 1300-1600 rpm / min; Preferably, the mixing time in step (2) is 10-30 min; Preferably, in step (2), the particle size D50 of the second lithium cobalt oxide sintered product is 4-8 μm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: Step (2) The second lithium cobalt oxide sintered product is prepared by the following method: Mixing a lithium source, a second cobalt source and a dopant and performing secondary calcination to obtain the second lithium cobaltate calcined product; Preferably, the secondary calcination is carried out at a temperature of 900-1100° C., for a time of 6-12 hours, in an air atmosphere or an oxygen atmosphere.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The mixing speed in step (3) is 200-400 rpm / min; Preferably, the mixing time in step (3) is 10-20 min; Preferably, in step (3), the mass ratio of the first mixture to the second mixture is (5-9):(1-5); Preferably, the sintering temperature in step (3) is 800-1000° C., the sintering time is 5-16 hours, and the atmosphere is air atmosphere or oxygen atmosphere.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) mixing a coating agent and a first lithium cobalt oxide sintered product having a particle size D50 of 16-19 μm at a speed of 1300-1600 rpm / min for 10-30 min, wherein the mixing speed is 3.25-8 times the mixing speed in step (3), to obtain a first mixture; The first lithium cobalt oxide sintered product is prepared by the following method: a lithium source, a first cobalt source and a dopant are mixed, and then calcined at a temperature of 1000-1200° C. for 6-12 hours in an air atmosphere or an oxygen atmosphere to obtain the first lithium cobalt oxide sintered product; (2) mixing the coating agent and the second lithium cobalt oxide calcined product having a particle size D50 of 4-8 μm at a speed of 1300-1600 rpm / min for 10-30 min, wherein the mixing speed is 3.25-8 times the mixing speed of step (3), to obtain a second mixture; The second lithium cobalt oxide sintered product is prepared by the following method: a lithium source, a second cobalt source and a dopant are mixed, and then calcined at a temperature of 900-1100° C. for 6-12 hours in an air atmosphere or an oxygen atmosphere to obtain the second lithium cobalt oxide sintered product; Based on the total mass of the first lithium cobalt oxide sintered product in step (1) and the second lithium cobalt oxide sintered product in step (2), the total amount of the coating agent in step (1) and the coating agent in step (2) is 4-10wt%; the ratio of the amount of the coating agent in step (1) to the amount of the coating agent in step (2) is the same as the ratio of the specific surface area of the first lithium cobalt oxide sintered product in step (1) to the second lithium cobalt oxide sintered product in step (2); (3) mixing the first mixture of step (1) and the second mixture of step (2) at a mass ratio of (5-9):(1-5) at a speed of 200-400 rpm / min for 10-20 min, and then sintering at a temperature of 800-1000° C. for 5-16 h in an air atmosphere or an oxygen atmosphere to obtain the lithium cobalt oxide positive electrode material; There is no particular order in which steps (1) and (2) are performed.
9. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobalt oxide positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium cobalt oxide positive electrode material as claimed in claim 9.
Citation Information
Cited By
Coated modified lithium cobalt oxide material, preparation method thereof, positive electrode and lithium ion battery
CN120622554A
Coated modified lithium cobalt oxide material, preparation method thereof, positive electrode and lithium ion battery
CN120622554B
Lithium cobalt oxide composite material and preparation method thereof, positive plate and lithium ion battery
CN121054661A
Lithium cobalt oxide positive electrode material and preparation method and application thereof
CN121149207A
Composite positive electrode material and preparation method and application thereof
CN121149208A